Neutrophilic-chronic myeloid leukemia: A case report - Al Ghasham, Nahlah S. (Int J Health Sci (Qassim), 2015)
Neutrophilic-chronic myelogenous leukemia (CML-N) is a rare chronic myelogenous leukemia (CML) variant characterized by BCR-ABL1 positive chronic neutrophilia. It has a BCR breakpoint on chromosome 22 between exons 17 and 20 in a region designated as micro-BCR. It is thought to have a more benign course than classical CML. This case report describes a 41-year-old Saudi woman diagnosed with CML-N. The peripheral blood and bone marrow picture for her were dominated by segmented neutrophils and fluorescent in situ hybridization was positive for BCR/ABL fusion of t(9;22). Our patient eventually required a stem cell transplant because of imatinib intolerance and bone marrow failure believed to be induced by nilotinib.